KINERJA INVESTASI REKSADANA SELAMA PANDEMI COVID 19 - Ade Eka Puspitasari; Kukuh Wahyu; Vera Ameira (Jurnal Pijar, 2023)
Investment is a way of putting in a certain amount of money in order to get profits in the future. Investment activity in the capital market is an economic activity that is in great demand by the public, which in its development is very vulnerable to macroeconomic conditions in general. Mutual funds are schemes to raise money from capital owners managed by a professional (investment manager) to invest in stocks. The profits that mutual fund investors get are the same as stock investments that they do themselves, namely dividends. Mutual funds can be an easy choice for novice investors who want to invest in stocks. Mutual funds are also the right choice for owners of large amounts of capital because they don't need to monitor them frequently and still have the opportunity to make a profit. Mutual fund investment can be an option for financial preparation in the future. This is recommended because mutual fund investment is a form of investment that has a promising return and is higher than other financial management such as deposits or gold.Keywords: investment, performance, mutual funds, capital market.